Decoding An Automobile’s Technical Specification From Its Identification Number - Mačiūnas, Mantas; Skorniakov, Viktor (Vilnius University Open Series, 2025)
We propose a method for decoding technical vehicle‘s parameters (make, model name, body type etc.) from its identification number. Classification is done for the entire specification at once, thus utilising the underlying dependencies between labels. To achieve the goal, several models were used – nearest neighbours, decision tree, extra trees and random forest classifiers.
Keywords: vehicle identification number; multi-label classification; random forest classifier; decision tree classifier; extra trees classifier; k-nearest neighbours classifier